2017
DOI: 10.3892/etm.2017.4892
|View full text |Cite
|
Sign up to set email alerts
|

Weikangning therapy in functional dyspepsia and the protective role of Nrf2

Abstract: Functional dyspepsia (FD) is a non-organic gastrointestinal disorder that has a marked negative impact on quality of life. Compared with conventional pharmacological therapies, the traditional Chinese medicine weikangning (WKN) is a safe and effective treatment for FD. The present study aimed to determine the molecular mechanisms underlying the efficacy of WKN. The effect of different concentrations of WKN on the proliferation of the human gastric mucosal epithelial cell line GES-1 was assessed. The optimal WK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…More ROS will be produced after mitochondrial injury, which accelerates cell apoptosis [ 6 ]. Evidence demonstrated that oxidative stress-induced damage in gastric mucosal epithelial cells is related to the pathogenesis and development of FD [ 7 ]. Antioxidant agent mitoTEMPO showed gastroprotection by preventing mitochondrial apoptosis and mitochondrial oxidative stress-mediated proinflammation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More ROS will be produced after mitochondrial injury, which accelerates cell apoptosis [ 6 ]. Evidence demonstrated that oxidative stress-induced damage in gastric mucosal epithelial cells is related to the pathogenesis and development of FD [ 7 ]. Antioxidant agent mitoTEMPO showed gastroprotection by preventing mitochondrial apoptosis and mitochondrial oxidative stress-mediated proinflammation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that Banxia Xiexin Decoction could effectively improve the total dyspepsia symptom score and the single dyspepsia symptom score of FD patients, without adverse reactions. Chang et al used Weikangning Capsule to treat patients with FD ( Chang et al, 2017 ). The results showed that Weikangning Capsule can significantly improve the clinical symptoms of patients with FD compared with western medicines, and can improve the mood of patients to a certain extent, alleviate anxiety and depression psychological disorders, and improve the quality of life.…”
Section: Therapeutic Effect Of Tcm On Fd and Its Related Mechanismsmentioning
confidence: 99%
“…The Xiaoyao pill improved the Hamilton Rating Scale for Depression score, motilin and gastrin levels, as well as the rate of gastric emptying 10 . Though some action modes of TCMs have been revealed 7 , further investigations are still needed to determine their precise functionary mechanisms and find new intervention targets. Moreover, due to the complexity of multiple constituents from TCMs, accompanied by complicated synergistic effect processes, their precise localization in the clinic is also ambiguous, thus hindering their widespread use.…”
Section: Introductionmentioning
confidence: 99%